Human Rights - The Rights of the Child - Smyczyński, Tadeusz; Andrzejewski, Marek (Quintessence Monographs Series, 2025)
This monograph stands as a uniquely valuable legal work, shedding light on the emergence of children’s rights – not only through its professional rigor but also through the deeply personal dimension that stems from the long-standing friendship and collaboration between Professors Tadeusz Smyczyński and Professor Andrzejewski. The entire work bears the unmistakable “Polish touch,” proudly rooted in the intellectual traditions and cultural values of Poland, where the family is recognized as the bedrock of society and the principal guardian of each child’s well-being. The Polish touch that led to the birth of the United Nations Convention on the Rights of the Child (CRC). The monograph is anchored in the CRC, with Professor Smyczyński, drafter of the Convention’s initial version in 1978, sharing his unique insights and guiding the reader through his reasoning, value judgments, and the ethical principles that shaped the foundational document. Polish legal scholars and initiatives, as highlighted throughout this volume, played a pivotal role in driving the global recognition of the need for a specific convention dedicated to children’s rights, based on the understanding that children, with their special needs and qualities, require distinctive care and respect. Despite centuries in which children were seen and treated as miniature adults, it was in large part thanks to Polish scholarship and advocacy for family values that a decisive shift in attitudes and legal standards occurred – a legacy this monograph celebrates. Through its systematic, historically informed approach, the work explores not only the evolution of children’s rights and the definition of the child, but also the indispensable role of the family. Professor Andrzejewski’s critical assessment of the practical applicability of children’s rights further demonstrates how, even amidst a comprehensive modern legal framework, children’s vulnerability endures – especially in an age where moral values and concepts of human dignity are under challenge. What makes this monograph especially compelling is the harmonious blend of professional scholarship and heartfelt compassion that reflects the close friendship of its authors, both united by a profound desire to protect all children. Their joint endeavor is a testament to the belief that enduring personal bonds, shared convictions, and the enduring strength of family values can – and must – drive the ongoing advancement of children’s rights, both in Poland and throughout the world.